Searching for the universal subconscius : study on music and emotion - Seppä, Antti (2010)
Are there any differences in how we feel about music? This research reaches to clarify differences and their reasons in our perception of music-related emotions. Furthermore, this research presents two new measuring tools for how to consider music-related emotions and musical preferences, The Eye of Emotions and The Indicator of Interest. The first aim of this study was to test the above-mentioned models in practice. Both of these new models capture together the categorical and dimensional ways of thinking about music-related emotions. The Eye of Emotions gives us information about which of the given qualities is the most important to the participant (in relation to the heard musical excerpt) and in what intensity the emotional quality is experienced. The model is based on a combination of valence and arousal axis of a dimensional model and the basic emotions. The Indicator of Interest does the same with the most commonly used terms of interest and liking. The goal of using these two scales of measurement was to get exact knowledge about participants’ experience in four different dimensions; quality and the amount of experienced emotions, experienced aesthetical value and the amount of liking. The second aim of this research was to find out if the participants’ aesthetic distance, for example musical history, age, gender and preferences, would be related with the emotions experienced during the test. In most cases the participants reported very similar emotional listening experiences despite of the differences in their current emotional state or musical background. In addition to the two main research questions, this study reflects to the growing amount of research on the field opening aspects to the most important questions on the matter, such as what is an emotion? Are we able to recognize an emotion without feeling it and with what mechanism? Do emotions change during the human development or is it just our growing ability to communicate about the surrounding existence that develops during the years? There does not seem to be a consensus on the basic issues in this field.